Comparative environmental impacts of source-separation systems for domestic wastewater management in rural China. (1st October 2015) - Lam, Lauho; Kurisu, Kiyo; Hanaki, Keisuke
Abstract: To address issues of poor sanitation and water scarcity in developing countries, innovative wastewater management systems should be proposed, based on considerations of life cycle and local environmental impacts. Source-separation separates urine, feces, and gray water, enhancing the reuse of nutrients, and is considered a promising wastewater treatment method. This study evaluates the life cycle and local environmental impacts of source-separation systems. Each system was set to achieve the same effluent quality as the functional unit. Four scenarios were examined: offsite treatment (B1), onsite treatment (B2), source-separation (A1), and pour-flush toilet use (A2). The study area was a hypothetical village in the municipality of Tianjin in China, which has experienced severe water shortages and poor sanitation. Life cycle impacts such as global warming, acidification, and eutrophication were evaluated using a life cycle assessment (LCA) framework, and direct water use was evaluated as the local impact. The scenarios enhancing nutrient recovery (B2 and A2) showed significant benefit by avoiding mineral fertilizer use; however, the source-separation system (A1) showed the best performance in terms of life cycle environmental impacts, which supports the findings of several previous LCA studies with similar system boundaries. Within the selected framework and assumptions, the results show that the source-separation system had the best environmental performance in terms of direct water use and the lifecycle impact categories. Graphical abstract: Highlights: Life cycle analysis and direct water use of four wastewater treatment scenarios. Offsite activated sludge, onsite johkasou, source-separation, and pour-flush toilet. Processes were designed to obtain the same effluent quality from each scenario. Source-separation performed best for global warming, acidification, eutrophication. Source-separation also had lowest direct water use.